2004
DOI: 10.1177/135676670301000103
|View full text |Cite
|
Sign up to set email alerts
|

Individualism/collectivism as a moderating factor to the self-image congruity concept

Abstract: Self-image congruity, the relationship between one’s self-image and one’s image of a product or service, is a widely accepted consumer behaviour theory lately finding currency in tourism literature. For tourism, as a global industry involving international tourists from varied cultural backgrounds, it is important to explore how the theory holds across a broad spectrum of cultures. To test the concept’s cross-cultural applicability, an exit survey which overlaid the concept of self-image congruity with Geert H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
71
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(82 citation statements)
references
References 28 publications
2
71
1
Order By: Relevance
“…Personal-oriented consumers seek to gain self-directed pleasure from luxury consumption by focusing on the achievement of hedonic gratification and self-awareness rather than pleasing others' expectations (Tsai, 2005). Personal-oriented consumption can be conceptualized as contrasting to the motivations of collectivists consumers, who are less likely to place emphasis on achieving personal goals to enhance self-image (Litvin & Kar, 2004). It follows that in individualistic cultures such as the US and the UK, personal value perceptions may have a particularly strong impact on luxury consumption.…”
Section: Personal Value Perceptionsmentioning
confidence: 99%
“…Personal-oriented consumers seek to gain self-directed pleasure from luxury consumption by focusing on the achievement of hedonic gratification and self-awareness rather than pleasing others' expectations (Tsai, 2005). Personal-oriented consumption can be conceptualized as contrasting to the motivations of collectivists consumers, who are less likely to place emphasis on achieving personal goals to enhance self-image (Litvin & Kar, 2004). It follows that in individualistic cultures such as the US and the UK, personal value perceptions may have a particularly strong impact on luxury consumption.…”
Section: Personal Value Perceptionsmentioning
confidence: 99%
“…Due to the interdependence within groups, collectivists give priority to the goals of their groups, which strongly influence individuals' behaviors (Triandis, 2001;Litvin and Kar, 2004). In addition, they tend to be flexible, quickly adapt to social contexts, and preserve others' reputation so as to create a harmonious interpersonal atmosphere and keep social relationships (Park, 1998;Suh, 2002;Sung and Tinkham, 2005).…”
Section: The Impacts Of Culture On Customer Behavior In Koreamentioning
confidence: 99%
“…Since Chon's (1992) original study, several others have sought to empirically validate selfcongruity theory in the context of tourism destinations. For example, in a replication of Chon's original (1992) study, Litvin and Goh (2003) investigated whether actual and ideal self-congruity influenced the satisfaction of tourists departing Singapore. Results indicated that, at the aggregate level, visitors who felt Singapore as a destination closely matched the way they saw themselves ('actual self') and the way they would like to be seen ('ideal self') were also more satisfied with their tourist experience than those with low levels of selfcongruity.…”
Section: Self-congruity Theory In Tourismmentioning
confidence: 99%